1995
DOI: 10.2105/ajph.85.7.949
|View full text |Cite
|
Sign up to set email alerts
|

US mortality by economic, demographic, and social characteristics: the National Longitudinal Mortality Study.

Abstract: OBJECTIVES. A large US sample was used to estimate the effects of race, employment status, income, education, occupation, marital status, and household size on mortality. METHODS. Approximately 530,000 persons 25 years of age or more were identified from selected Current Population Surveys between 1979 and 1985. These individuals were followed for mortality through use of the National Death Index for the years 1979 through 1989. RESULTS. Higher mortality was found in Blacks than in Whites less than 65 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
330
2
19

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(370 citation statements)
references
References 19 publications
(4 reference statements)
19
330
2
19
Order By: Relevance
“…In addition, greater cumulative IPV exposure was associated with worse self-rated health, which has been shown to be a good indicator of subsequent morbidity and mortality (Fryers et al, 2003;McDonough et al, 1997;Ren et al, 1999;Sorlie et al, 1995). Greater cumulative IPV exposure was also associated with the likelihood that self-reported symptoms met the diagnostic criteria for PTSD, as well as the likelihood that the respondents' physical health and emotional problems interfered with their work.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, greater cumulative IPV exposure was associated with worse self-rated health, which has been shown to be a good indicator of subsequent morbidity and mortality (Fryers et al, 2003;McDonough et al, 1997;Ren et al, 1999;Sorlie et al, 1995). Greater cumulative IPV exposure was also associated with the likelihood that self-reported symptoms met the diagnostic criteria for PTSD, as well as the likelihood that the respondents' physical health and emotional problems interfered with their work.…”
Section: Discussionmentioning
confidence: 97%
“…It is well established that low-income individuals, especially the persistently poor (i.e., individuals who earn less than $20,000 for 4 years or more), have high rates of mortality and morbidity (Geronimus, 1992;Krieger, Rowley, Herman, Avery, & Phillips, 1993;McDonough, Duncan, Williams, & House, 1997;Ren, Benjamin, & Williams, 1999;Sorlie, Backlund, & Keller, 1995). Studies have also found an association between low income and compromised mental health among women, such as affective disorders, anxiety disorders, and nonaffective psychosis (Fryers, Melzer, & Jenkins, 2003;Kessler et al, 1994;Regier et al, 1993;Robbins, Locke, & Regier, 1991;Williams, Takeuchi, & Adair, 1992).…”
Section: Welfare Receipt and Health Statusmentioning
confidence: 99%
“…See for example, Pappas et al (1993), Sorlie, Backlund and Keller (1995), Deaton and Paxson (1999), Deaton (2001). Essentially all of this analysis is based on estimating the correlation between the probability of a negative health outcome and income.…”
Section: Correlation Between Income and Bmi The Conditional Meanmentioning
confidence: 99%
“…Morbidity and mortality rates vary greatly by markers of socioeconomic position, including education, income, and occupation (Davey Smith, Shipley & Rose, 1990;Sorlie, Backlund & Keller, 1995;Pappas, Queen, Hadden & Fisher, 1993). The strong negative association between socioeconomic factors and health status has been observed across a wide variety of historical contexts, geographic locations, and populations (Blaxter 1987;Haan, Kaplan & Syme, 1989;Link & Phelan, 1995;Lynch & Kaplan, in press).…”
Section: Introductionmentioning
confidence: 99%